Makna Etika Kerja Bagi Kesehatan Mental Karyawan: Studi Pada Ox Coffee - Berkat Jaya Zalukhu; Rizka Putri; Irwan Harefa; Sarah Siregar; Bayu Teta (Jurnal Bisnis Inovatif dan Digital, 2025)
This study aims to explore the meaning of work ethics in relation to employees’ mental health within the café industry, with a specific focus on Ox Coffee in Medan. Utilizing a descriptive qualitative approach, data were collected through in-depth interviews with five permanent employees across various roles. The findings indicate that the application of work ethics at Ox Coffee encompasses discipline, responsibility, open communication, customer service, and skills development. Employees perceive work ethics as a guide for managing job-related stress, a foundation for psychological well-being, a contributor to professional identity, and a mechanism for reducing workplace conflict and tension. Key factors such as fairness in task distribution, constructive communication, recognition of employee contributions, and work-life balance were found to significantly influence mental health. The study recommends strategies including the development of a supportive and inclusive work culture, skills training, effective communication systems, and mental health programs to foster a psychologically healthy workplace in the café sector.